LEARNING SOLUTIONS - IGUAL - Ion, Mierlus Mazilu (European Scientific Journal, ESJ, 2013)
The low quality of primary and secondary education in most Latin America countries is a well-known problem. As a response to this reality, the private educational market has been steadily growing in those countries. These private schools, in general, offer a higher quality and personalized education for the students that can afford it. The main selling point of these institutions is access to better resources: better teachers, technologies, materials and pedagogical methods. This difference in education quality creates a problem once students from public schools reach university. This IGUAL project will generate learning solutions (combination of e-learning software, pedagogical methodologies and learning materials) to facilitate the assimilation of new knowledge and the development of new skills even when the student has deficient background knowledge and/or underdeveloped required skills. The solutions that this project will provide have the potential to be used by all students in the Latin American